Positive end-expiratory pressure increases intracranial pressure but not pressure reactivity index in supine and prone positions: a porcine model study - Hammervold, Rønnaug; Beqiri, Erta; Smielewski, Peter; Storm, Benjamin S.; Nielsen, Erik W.; Guérin, Claude; Frisvold, Shirin K. (Frontiers in Medicine, 2025)
IntroductionPositive end-expiratory pressure (PEEP) and prone positioning can improve gas exchange by promoting uniform lung aeration. However, elevated ventilation pressures may increase intracranial pressure (ICP) and disrupt cerebral autoregulation. This study investigated the effects of PEEP on ICP and cerebral autoregulation in a porcine model with healthy lungs and normal ICP, comparing prone and supine positions. Cerebral autoregulation was assessed through cerebrovascular reactivity using the pressure reactivity index (PRx). We also explored whether other baseline variables influenced potential variances in ICP and PRx.MethodologyTwelve anesthetized pigs were randomized to begin in either supine or prone position, across PEEP of 5, 10, 15, and 20 cmH2O. Continuous monitoring included esophageal pressure to calculate end-inspiratory and end-expiratory transpulmonary pressures. The ICM+® software (University of Cambridge Enterprise, Cambridge, United Kingdom) was used for high-resolution data collection, signal processing and ICP curve analysis. Linear mixed-effects models and ANOVA were used to analyze changes in ICP and PRx and the influence of position. An exploratory correlation analysis was conducted on baseline variables potentially related to the ICP increase.ResultsMean ICP increase was 1.0 mmHg ± 0.9 at 10 cmH2O PEEP, 2.0 mmHg ± 1.7 at 15 cmH2O PEEP, and 3.1 mmHg ± 1.6 at 20 cmH2O PEEP compared to a baseline PEEP of 5 cmH2O (p < 0.001). The effect of PEEP increase on ICP was not influenced by body position. PRx remained unaffected by PEEP. PEEP-induced increases in ICP were higher in cases of higher baseline ICP, higher central venous pressure, lower respiratory system elastance and lower end-inspiratory and end-expiratory transpulmonary pressures.ConclusionIncreasing PEEP elevates ICP regardless of body position without adversely affecting cerebral autoregulation in a healthy porcine model. Baseline ICP, central venous pressure, respiratory system elastance and end-inspiratory and end-expiratory transpulmonary pressure may influence the magnitude of ICP changes.